HRM specificities’ on Portugal hotel units - Silva, Susana (2016)
This paper presents the main Human Resources Management (HRM) specificities’ on Portuguese hotel units. We try to understand the role of HRM on behavior of co-workers and quality service in hotel units and to know the future tendency of human capital profile on Portuguese hotel units and the role of HRM function on management of their staff. We, also, try to explore if Portuguese culture has influence on HRM specificities’ of hotel units. This phenomenon has a special relevance in the Portuguese context, because this country is known a growing process of tourism industry in recent years. Furthermore, little is known about HRM department’ contributions to their human capital management and development. This paper is one of the first to focus specifically on Portuguese hotel units and it also seeks to present findings that stem from the Human Resources Managers’ perspective. The paper is based on qualitative case studies. The data were collected through semi-structured interviews of 12 human resource managers from 12 hotel units located in Portugal. The results show that although there is not an effective HRM, current HRM practices are enough to encouraging pro-environmental behavior in their staff and they have a direct effect on customer satisfaction and competitiveness of sector. However, managers recognize there is need introduce some change on short-term to promote a better performance of staff with effect on customers satisfaction and competitiveness on sector in Portugal. According to these results, the paper discusses the major theoretical and practical implications.